AlkB RNA demethylase homologues and N6‐methyladenosine are involved in Potyvirus infection. (14th June 2022) - Yue, Jianying; Wei, Yao; Sun, Zhenqi; Chen, Yahan; Wei, Xuefeng; Wang, Haijuan; Pasin, Fabio; Zhao, Mingmin
Abstract: Proteins of the alkylation B (AlkB) superfamily show RNA demethylase activity removing methyl adducts from N 6 ‐methyladenosine (m 6 A). m 6 A is a reversible epigenetic mark of RNA that regulates human virus replication but has unclear roles in plant virus infection. We focused on Potyvirus —the largest genus of plant RNA viruses—and report here the identification of AlkB domains within P1 of endive necrotic mosaic virus (ENMV) and an additional virus of a putative novel species within Potyvirus . We show that Nicotiana benthamiana m 6 A levels are reduced by infection of plum pox virus (PPV) and potato virus Y (PVY). The two potyviruses lack AlkB and the results suggest a general involvement of RNA methylation in potyvirus infection and evolution. Methylated RNA immunoprecipitation sequencing of virus‐infected samples showed that m 6 A peaks are enriched in plant transcript 3′ untranslated regions and in discrete internal and 3′ terminal regions of PPV and PVY genomes. Down‐regulation of N. benthamiana AlkB homologues of the plant‐specific ALKBH9 clade caused a significant decrease in PPV and PVY accumulation. In summary, our study provides evolutionary and experimental evidence that supports the m 6 A implication and the proviral roles of AlkB homologues in Potyvirus infection. Abstract : AlkB RNA demethylases remove methyl adducts from N 6 ‐methyladenosine. We provide evolutionary and experimental evidence that supports the proviral roles of AlkB homologues in Potyvirus infection.